Effect of Asbestos on Anti-Tumor Immunity and Immunological Alteration in Patients with Malignant Mesothelioma - Nishimura, Yasumitsu; Maeda, Megumi; Kumagai-Takei, Naoko; Matsuzaki, Hidenori; Lee, Suni; Fukuoka, Kazuya; Nakano, Takashi; Kishimoto, Takumi; Otsuki, Takemi (IntechOpen, 2012)
None